Encoding-Decoding-Based control and filtering of networked systems: insights, developments and opportunities - Wang, Zidong; Wang, Licheng; Liu, Shuai; Wei, Guoliang (IEEE/CAA journal of automatica sinica, 2018)
In order to make the information transmission more efficient and reliable in a digital communication channel with limited capacity, various encoding-decoding techniques have been proposed and widely applied in many branches of the signal processing including digital communications, data compression, information encryption, etc. Recently, due to its promising application potentials in the networked systems &#x0028 NSs &#x0029, the analysis and synthesis issues of the NSs under various encoding-decoding schemes have stirred some research attention. However, because of the network-enhanced complexity caused by the limited network resources, it poses new challenges to the design of suitable encoding-decoding procedures to meet certain control or filtering performance for the NSs. In this survey paper, our aim is to present a comprehensive review of the encoding-decodingbased control and filtering problems for different types of NSs. First, some basic introduction with respect to the coding-decoding mechanism is presented in terms of its engineering insights, specific properties and theoretical formulations. Then, the recent representative research progress in the design of the encodingdecoding protocols for various control and filtering problems is discussed. Some possible further research topics are finally outlined for the encoding-decoding-based NSs.